Redescription of Polichnodes americana Giglio-Tos, 1898 (Orthoptera: Tettigoniidae) with a new record and habitat notes from Brazilian Amazon Rainforest - de Mello Mendes, Diego Matheus; Sobral, Rafael; Da Silva Neto, Alberto Moreira (Zootaxa, 2019)
In this work it was made the redescription of male of Polichnodes americana including new traits as internal genitalia and morphology of stridulatory files. Also it was recorded for the first time the distribution of this species to Brazil, in Amazonas, and notes on habitat.